Bedazzled: a new, striking species of Corades from the outskirts of Quito questions our knowledge of Andean cloud forest butterflies (Lepidoptera, Nymphalidae, Satyrinae) - Pyrcz, Tomasz W.; Boyer, Pierre; Petit, Jean-Claude; Garlacz, Rafał; Garlacz, Kamila S. Zając-; Espeland, Marianne; Willmott, Keith R. (Zootaxa, 2024)
A new butterfly species in the genus Corades, C. yanacocha Pyrcz, Boyer & Petit sp. n., belonging to the diverse, predominantly Andean subtribe Pronophilina (Nymphalidae, Satyrinae), is described from the Yanacocha Reserve situated only a couple of kilometres west of Quito, Ecuador. This is an extremely surprising discovery in a region whose butterfly fauna was considered to be fairly well known, underlying the need to protect remnants of high elevation forests in such overpopulated regions of the Andes. Morphological characters, in particular male genitalia, indicate an affinity of C. yanacocha sp. n. with C. trimaculata from northern Peru. A preliminary molecular study using COI barcodes indicates, however, the widely distributed north Andean C. dymantis as the closest relative.